2014
DOI: 10.1371/journal.pone.0098624
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of a Preclinical Model of Breast Cancer Lung Micrometastatic to Macrometastatic Progression

Abstract: Most cancer patients die with metastatic disease, thus, good models that recapitulate the natural process of metastasis including a dormancy period with micrometastatic cells would be beneficial in developing treatment strategies. Herein we report a model of natural metastasis that balances time to complete experiments with a reasonable dormancy period, which can be used to better study metastatic progression. The basis for the model is a 4T1 triple negative syngeneic breast cancer model without resection of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 41 publications
1
57
0
Order By: Relevance
“…To determine the effect of AG311 on necrosis in vivo, BALB/cJ mice were implanted with nonfluorescent 4T1 tumor cells. The experiment was performed as published (Bailey-Downs et al, 2014) with the following modifications: cell suspension (7500 cells/100 ml) in phosphate-buffered saline with 1 mM EDTA was implanted into the mammary fat pad #4 of 8-week-old female BALB/cJ mice. Three weeks after implantation when the average tumor size was ∼260 mm 3 , mice were separated based on matched tumor volumes (n 5 9-11).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the effect of AG311 on necrosis in vivo, BALB/cJ mice were implanted with nonfluorescent 4T1 tumor cells. The experiment was performed as published (Bailey-Downs et al, 2014) with the following modifications: cell suspension (7500 cells/100 ml) in phosphate-buffered saline with 1 mM EDTA was implanted into the mammary fat pad #4 of 8-week-old female BALB/cJ mice. Three weeks after implantation when the average tumor size was ∼260 mm 3 , mice were separated based on matched tumor volumes (n 5 9-11).…”
Section: Methodsmentioning
confidence: 99%
“…Next, the efficacy of AG311 was examined in a TNBC allograft metastatic progression model in immune proficient mice previously developed in our laboratory (Bailey-Downs et al, 2014). Dual luciferase/GFP 4T1-tagged (4T1-luc2-GFP) cells were implanted in female BALB/cJ mice.…”
Section: Ag311 Induces Necrosis In Breast Cancermentioning
confidence: 99%
“…Interestingly, Bailey-Down et al . [48] also showed that reducing the number of implanted 4T1 cells increased metastatic efficiency. Nevertheless, in animals inoculated with a cell density equal or lower than 1500, the tumor take rate was lower than 50% and macrometastases were barely observed at five weeks post-implantation [48], in contrast with results reported herein.…”
Section: Discussionmentioning
confidence: 99%
“…[48] also showed that reducing the number of implanted 4T1 cells increased metastatic efficiency. Nevertheless, in animals inoculated with a cell density equal or lower than 1500, the tumor take rate was lower than 50% and macrometastases were barely observed at five weeks post-implantation [48], in contrast with results reported herein. In the work of Bailey-Down et al ., the best compromise between tumor take rate (over 90%) and metastatic efficiency (67% in the lungs) was achieved upon inoculation of 7500 4T1 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation